Playing in Minecraft: an exploratory study - Petry, Arlete dos Santos (Revista FAMECOS, 2018)
Departing on a review of the literature, this article discusses, grounded on critical theory, the overlap and the boundaries between play/entertainment and work/learning concerning to digital games. In addition, it tries to find what is core in the distinction between play as entertainment and play as work. The review shows a dissent, understanding the phenomenon either as a sort of work, or as a voluntary choice for entertainment, or as a phenomenon on which the boundaries between work and entertainment are blurred. Differently from the mentioned researches, whose data were obtained with adults and young people, this empirical study was carried out with children, being also a unique work with so young people in this very complex question. Being a first approach and occurring with a small number of children, the research was set up as an exploratory study using participant observation and interviewing for the data collection, and discourse analysis and Likert scale for the discussion of outcomes.